Discrimination of enantiomers of dipeptide derivatives with two chiral centers by tetraaza macrocyclic chiral solvating agents using 1H NMR spectroscopy. Issue 12 (5th October 2016) - Fang, Lixia; Lv, Caixia; Wang, Guo; Feng, Lei; Stavropoulos, Pericles; Gao, Guangpeng; Ai, Lin; Zhang, Jiaxin
Abstract : Enantiomers of dipeptide derivatives with two chiral centers were effectively discriminated by a new class of tetraaza macrocyclic chiral solvating agents via 1 H NMR spectroscopy. Abstract : 1 H NMR spectroscopy is often used to discriminate enantiomers of chiral analytes and determine their enantiomeric excess (ee) by various chiral auxiliaries. In reported research, these studies were mainly focused on chiral discrimination of chiral analytes with only one chiral center. However, many chiral compounds possessing two or more chiral centers are often found in natural products, chiral drugs, products of asymmetric synthesis and biological systems. Therefore, it is necessary to investigate their chiral discrimination by effective chiral auxiliaries using 1 H NMR spectroscopy. In this paper, a new class of tetraaza macrocyclic chiral solvating agents (TAMCSAs) with two amide (CONH), two amino (NH) and two phenolic hydroxyl (PhOH) groups has been designed and synthesized for chiral discrimination towards dipeptide derivatives with two chiral centers. These dipeptide derivatives are important chiral species because some of them are used as clinical drugs and special dietary supplements for treatment of human diseases, such asl -alanyl-l -glutamine and aspartame. The results show that these TAMCSAs have excellent chiral discriminating properties and offer multiple detection possibilities pertaining to 1 H NMR signals of diagnostic split protons. The nonequivalent chemical shifts (up to 0.486 ppm) of various types of protons of these dipeptide derivatives were evaluated with the assistance of well-resolved 1 H NMR signals in most cases. In addition, enantiomeric excesses (ee) of the dipeptide derivatives with different optical compositions have been calculated based on integration of well-separated proton signals. At the same time, the possible chiral discriminating behaviors have been discussed by means of Job plots, ESI mass spectra and a proposed theoretical model of (±)-G1 with TAMCSA1c . Additionally, the association constants of enantiomers of (±)-G5 with TAMCSA1a were calculated by employing the nonlinear curve-fitting method.